WATER ABSORPTION BEHAVIOUR AND ITS EFFECT ON MECHANICAL AND THERMAL PROPERTIES OF CONTINUOUS UNIDIRECTIONAL PINEAPPLE LEAF FIBRE REINFORCED POLY LACTIC ACID COMPOSITES - Mustafa, Z.; Razali, A.S.; Sappa, A.A.A.; Fadzullah, S.H.S.M.; Malingam, S.D.; Ratanawilai, T. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Pineapple leaf fibre (PALF) is hydrophilic material and prone to humidity absorption. The present moisture may alter the initial properties of natural fibre-based composite and it became more deleterious when using high fibre content. The objective of this paper investigates the water absorption behaviour and its effects on the mechanical and thermal properties of unidirectional PALF-reinforced polylactic acid (PLA) composites. The PLA composites with high content fibre (40 to 80 wt.%) of aligned PALF were prepared using a novel method combining pre-pregging and compression moulding followed by water immersion for 43 days. Composites showed significant saturation weight gains and diffusion coefficients than neat PLA, which increased from 0.46 to 19.22 cm2/s indicating that the presence of PALF fibre induced higher water absorption due to their hydrophilic nature. The initial tensile strength of the composites is up to 213.0 MPa, approximately 500% higher than neat PLA (33.56 MPa). The composite shows significant degradation up to 64 % and 68% in tensile and modulus after the ageing process and is influenced by the PALF fibre contents. Morphology analysis shows the presence of micro-cracks and voids due to the degradation of PLA and debonding of PALF and PLA after ageing. Crystalline contents of the materials increased up to 33% due to hydrolysis upon exposure to the water.